Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/6715275
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term High-NaCl Dietary Intake Changes Leukocyte Expression of VLA-4, LFA-1, and Mac-1 Integrins in Both Healthy Humans and Sprague-Dawley Rats: A Comparative Study

Abstract: This study is aimed at assessing the effects of a short-term high-salt (HS) diet on the peripheral blood leukocyte (PBL) activation status in healthy rats and young human individuals. Distribution of PBL subpopulations and surface expression of integrins were determined using flow cytometry in 36 men and women on a 7-day low-salt diet (<3.2 g salt/day) immediately followed by a 7-day HS diet (~14 g salt/day) or in Sprague-Dawley (SD) rats (n=24) on a 0.4% NaCl diet (aLS group) or a 4% NaCl diet (aHS group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In another human study, a short-term HS diet induced expansion of CD14 ++ CD16 + "intermediate" monocytes, which is associated with target organ inflammation in humans [22]. Our research group also demonstrated that a 7-day HS diet substantially altered the peripheral blood leukocytes' phenotype and dynamics, independently of BP changes in healthy individuals [21]. On the other hand, very little is known from human studies about HS diet induced changes of the adaptive immune responses, especially in terms of Th17/Treg interplay.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In another human study, a short-term HS diet induced expansion of CD14 ++ CD16 + "intermediate" monocytes, which is associated with target organ inflammation in humans [22]. Our research group also demonstrated that a 7-day HS diet substantially altered the peripheral blood leukocytes' phenotype and dynamics, independently of BP changes in healthy individuals [21]. On the other hand, very little is known from human studies about HS diet induced changes of the adaptive immune responses, especially in terms of Th17/Treg interplay.…”
Section: Introductionsupporting
confidence: 58%
“…Interestingly, there are evidences that HS intake can cause abnormal interactions between leukocytes and endothelial cells [18], induce pro-inflammatory cytokines production [19], and modulate immune cell (mainly macrophages and T cells) [20,21] functions in healthy humans, but clinical studies on the earliest effects of salt loading on the immune system and how oxidative stress relates to these effects are scarce. For example, elevation in extracellular sodium concentration has led to CD14 ++ CD16 + cells expansion via a ROS-dependent manner, as revealed in vitro study [22].…”
Section: Introductionmentioning
confidence: 99%
“…direction nor sequence. The current hypothesized pathway is based on multiple experimental and mechanistic studies, showing that 1-2 week high-sodium interventions induce various effects on leukocyte subsets (in number as well as activation state), 5,[10][11][12]29 and revealing a causal role for leukocyte subsets and particularly granulocytes with regard to development and progression of cardiovascular and renal disease. 17,30 Statistically, granulocyte concentrations were able to serve as a potential mediator in our models, fitting the above-mentioned mechanistic ideas, but again, associations do not mean causality or causality could exist in other directions.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] High sodium consumption has differential effects on leukocyte subsets with regard to their absolute numbers as well as activation state, involving proinflammatory effects on monocytes, macrophages, and T-cells, among others. 5,[7][8][9][10][11][12] Less is known about the effects on the most abundant leukocyte subset in humans, namely neutrophilic granulocytes. In our randomized controlled trial investigating the effect of a one-to-two-week high-sodium diet on healthy males, circulating neutrophil counts increased by ≈20%-an effect that has not been linked to the deleterious effects of sodium consumption to date.…”
mentioning
confidence: 99%
“…Even though it is necessary for the proper functioning of the organism, the intake of dietary salt (sodium chloride; NaCl) should be maintained at under 5 g/per day according to the World Health Organization (WHO) [ 1 , 2 , 3 , 4 ]. A high salt intake and its detrimental effects have been extensively explored for several decades, considering its contribution to inflammation [ 5 , 6 , 7 ], cardiovascular disease development [ 8 , 9 ], and other related complications [ 10 , 11 ]. Salt intake causes hemodynamic and immune response changes and induces cell activation and cytokine production, leading to pro-inflammatory reactivity [ 5 , 7 , 12 , 13 ] and pro-atherogenic conditions [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%